1985
DOI: 10.1111/j.1439-0434.1985.tb04834.x
|View full text |Cite
|
Sign up to set email alerts
|

Source of Infection of Sunflower Plants by Diaporthe helianthi in Yugoslavia

Abstract: D. beliantbi shows a developmental rhythm similar to that of many plant pathogenic Ascomycotina: the anamorph develops during the summer and the teleomorph during winter. However, under conditions of high humidity D. belianthi can precociously complete the development of its ascomata in autumn. Perithccial differentiation and maturation d o not occur simultaneously.Conidiomata in epidermal and subepidermal tissues and ascomata located in the phloem system were seen in the same over-wintered sunflower stem detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…They concluded that the Diaporthe isolates that produced predominantly b-conidia were similar to D. helianthi, as described in Yugoslavia. However, they were not able to resolve inconsistencies in the description of the Diaporthe isolates found in Ohio in comparison with those from Yugoslavia (Mihaljčević et al 1985), particularly for those that produced predominantly a-conidia. In our study, D. helianthi isolates produced white, floccose, and dense mycelia, dark-brown colored, on PDA; size of b-conidia (20 to 35 by 0.5 to 2.7 µm) was consistent with Gulya et al (1997).…”
Section: Discussionmentioning
confidence: 91%
“…They concluded that the Diaporthe isolates that produced predominantly b-conidia were similar to D. helianthi, as described in Yugoslavia. However, they were not able to resolve inconsistencies in the description of the Diaporthe isolates found in Ohio in comparison with those from Yugoslavia (Mihaljčević et al 1985), particularly for those that produced predominantly a-conidia. In our study, D. helianthi isolates produced white, floccose, and dense mycelia, dark-brown colored, on PDA; size of b-conidia (20 to 35 by 0.5 to 2.7 µm) was consistent with Gulya et al (1997).…”
Section: Discussionmentioning
confidence: 91%
“…After overwintering, these infected stalks were able to infect newly formed flower stalks of carrot. In contrast, Mihalj cević et al (1985) were unable to infect sunflower with conidia of D. helianthi from overwintering pycnidia, but infections could be readily established with ascospores from overwintered perithecia. Our results indicate that conidia of D. adunca from pycnidia on overwintered P. lanceolata scapes are capable of infecting spikes through vertical splash dispersal during rain events ( Table 4).…”
Section: Overwinteringmentioning
confidence: 87%
“…Some Phomopsis spp. can be seedborne or overseason with (immature) pycnidia and/or perithecia on infected debris (Von Arx, 1951;Kulik, 1983Kulik, , 1984bMihalj cević et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Stem canker caused by P. helianthi started in the leaves of sunflowers. The systemic nature of the disease was recognized by Mihaljcevic et al. (1985).…”
Section: Discussionmentioning
confidence: 99%
“…(1991) gave a coarse cytological description of the infection process in naturally infected leaves, but detailed cytological and physiological investigations have not yet been reported. The systemic nature of the disease was recognized by Mihaljcevic et al. (1985).…”
Section: Introductionmentioning
confidence: 99%